Modeling of Infilled Frames With Openings - Asteris, Panagiotis G.; Giannopoulos, Ioannis P.; Chrysostomou, Christis (My University, 2012)
This work concerns an assessment of the behavior of infilled frames. The feasibility of possible immediate implementation of some recent developments both in analysis and design of infilled frames for practical design is investigated. It is now widely recognized that masonry infill panels used in reinforced concrete (R/C) frame structures, significantly enhance both the stiffness and the strength of the surrounding frame. However, their contribution is often not taken into account because of the lack of knowledge of the composite behaviour of the surrounding frame and the infill panel. Currently, Seismic Design Codes (EC8 - Part 1, ASCE 41-06) contain provisions for the calculation of stiffness of solid infilled frames mainly by modeling infill as a 'diagonal strut.' However, such provisions are not provided for infilled frames with openings. The present study, proposes analytical equations of the reduction factor, which is expressed as the ratio of the effective width of the diagonal strut of an infill with openings over that of the a solid infill, in order to be able to calculate the initial lateral stiffness of reinforced concrete (RC) frames with infills that have openings. The validity of the proposed equations is demonstrated by comparing our results against work done by various researchers.
Keywords: Earthquake resistant design; Reinforced concrete; Masonry